The Phenomenon of Trance in The Tradition of Kuda Lumping Arts in Jorong Wonorejo, Nagari Lubuk Gadang Selatan, South Solok Regency, West Sumatra Province - Pratama, Wahyu; Yurisman; Endrizal (Kirana Publisher (KNPub), 2024)
This study discusses the